Development guidelines for the operation of community enterprises into the Primary GMP A Case Study of Nan Malt Enterprise. - ปัญญโรจน์ ณัฐพันธ์; ดวงพิกุล กนกรัตน์; ศิริพรอัครชัย ธัญทิพย์ (RMUTL Journal of Business Administration and Liberal Arts, 2019)
The objectives of this study are 1) to study a problem and threat to the operation of Nan Malt community enterprise. 2) to study the evaluation of the performance of Primary GMP. 3) To determine the guidelines for the operation of community enterprises into Primary GMP for Nan Malt community enterprise.Tumbon Klang Wiang, Amphoe Wiang Sa, Nan province is a case study. The research model is qualitative and quantitative research. Applying concepts in organizational management and norms of primary production standards is a framework for research. And rely on observation techniques. GMP Compliance Interview The main members and / or representatives of the organization provide basic information. The results of this research are as follows: 1) The study of problems and obstacles of operation of Nan Malt community found that the financial management is the most important problem then the production management, Marketing Management, Organizational Structure. This is a critical condition for success in business operations. And 2) the results of the assessment of the production environment according to the Primary GMP criteria from the self-assessment showed that the average score was 49.83 (83.06%). When considering the topic, it was found that maintenance and cleaning had the lowest average scores. Causes of lack of knowledge of implement or standard of cleaning the building regularly. Include how to keep chemicals, cleaners or other chemicals. It is associated with the hygienic and labeling of the separate and safe. To continue improve and develop the production process and environment.